Decreased northern hemisphere precipitation from consecutive CO2 doublings is associated with significant AMOC weakening - X Zhang; D W Waugh; I Mitevski; C Orbe; L M Polvani (Environmental Research: Climate)
Previous studies found many climate properties such as northern hemisphere (NH) surface temperature and precipitation respond non-monotonically when CO _2 is increased from 1 × to 8 × CO _2 relative to pre-industrial levels. Here, we explore the robustness of the non-monotonicity in the NH precipitation response in 11 coupled climate models. Eight models show a decrease in NH precipitation under repeated CO _2 doubling, indicating that the non-monotonic response is a common but not universal result. Although common, the critical CO _2 level where the NH precipitation decrease first occurs differs widely across models, ranging from 2×CO _2 to 8×CO _2 . These models also show a prominent weakening in the Atlantic meridional overturning circulation (AMOC) at the same critical CO _2 level, with the AMOC weakening leading the precipitation decrease. The sensitivities of NH precipitation and the AMOC to CO _2 doublings are positively correlated, especially when the AMOC weakens beyond 10 Sv. This suggests that the differences in models’ AMOC response can explain their contrasting NH precipitation responses, where models with a large AMOC weakening have decreased NH precipitation. Regionally, this decrease in NH precipitation is the most prominent over the North Atlantic, Europe and the tropical Pacific. Our results suggest that special care must be taken with the use of pattern scaling to inform regional climate decision-making.